Using African proverbial folklore to understand the holistic poverty eradication framework in the Book of Proverbs - Kimilike, Lechion Peter (Old Testament essays, 2006)
Sample comments of dominant biblical studies of the Old Testament Book of Proverbs indicate a deep-seated and wide-spread conviction that the book has a conservative status quo framework. Such suggestions sometimes go so far as to give the impression of divine sanction of structural poverty in society. This is done through the spiritualization of the reality of poverty. Nevertheless, this article argues that the Old Testament Book of Proverbs when approached from an African perspective has a transformative framework. A close look at poverty proverbs in terms of the interpreter's African presuppositions and cultural expectations rereads some transforming possibilities which underlie poverty texts in the Book of Proverbs.